Mucin exocytosis: a major target for Helicobacter pylori. Issue 3 (March 1993) - Micots, I; Augeron, C; Laboisse, C L; Muzeau, F; Mégraud, F
Abstract : AIMS: To determine whether Helicobacter pylori impairs the secretory function of mucous cells. METHODS: The mucus secreting human cell line CL. 16E, maintained as confluent monolayers on nitrocellulose filters, was infected with H pylori strain CIP 101260. After three hours of incubation with H pylori the monolayers were washed and reincubated with fresh culture medium for various time periods (24, 48, or 72 hours) before evaluating both the morphology and function of mucous cells. For morphological studies, epithelial monolayers were fixed in situ and processed for both standard histochemistry on paraffin wax sections, and electron microscopy. To measure mucins secreted from cultured cells, the cells were metabolically labelled with 3H-glucosamine. Undegraded mucins were quantitated as the radioactive glycoproteins blocked at the stacker gel interface after sodium dodecyl sulphate-polyacrylamide gel electrophoresis of the secretory glycoproteins. RESULTS: Control cultures of CL. 16E cells grew on filters as homogeneous monolayers of polarised mucous cells secreting a visco-elastic gel of mucins at the apical surface. In infected monolayers H pylori was in close contact with the apical surface of mucous cells. Cell counts and histological evaluation of the monolayers did not reveal any significant deleterious effect of H pylori on the mucous cells. H pylori induced only a modest inhibition of baseline mucus secretion from CL. 16E cells, this inhibition being significant only at 24 hours. In contrast, the mucus secretory response to two agents that raise intracellular cAMP and calcium--forskolin and ionophore A23187--was strongly inhibited. The inhibitory effect of H pylori on the exocytotic response was not paralleled by an inhibition of glycoprotein synthesis. CONCLUSION: Considering the fact that the exocytotic response to a variety of secretagogues constitutes the primary line of defence of the gastric mucosa in an emergency, it is suggested that H pylori exerts its deleterious effects by weakening this important physiological defence.